A Huey P. Newton story - Lee, Spike; Smith, Roger Guenveur; Newton, Huey P. (Thousand Oaks, CA : UrbanWorks Entertainment, 2004)
A dramatization of the life of Huey P. Newton, late co-founder of the Black Panther Party. Includes archival footage.
DVD, Dolby digital stereo.
Roger Guenveur Smith.
Based on the play by Roger Guenveur Smith.
MPAA rating: Not rated.
Keywords: African Americans -- Drama; Black Panther Party -- Drama; Newton, Huey P. -- Drama; Smith, Roger Guenveur -- Film and video adaptations; Biographical films